Inflatable Indian travel pillow as a pneumatic patient jack - Gopalakrishna A; Agrawal Karoon (Indian Journal of Plastic Surgery)
The Indian travel pillow readily available in the market has been utilized as a patient jack in the operation theatre. This has been used to raise the shoulders of an anaesthetized patient for surgery in the head and neck region and a set of two pillows have been used to prop-up a prone anaesthetized patient. This allows smooth positioning of the patient after intubation without disturbance to the airway with minimal manpower.